Further Evaluation of the Use of Multiple Schedules for Behavior Maintained by Negative Reinforcement. (March 2017) - Campos, Claudia; Leon, Yanerys; Sleiman, Andressa; Urcuyo, Beatriz
One potential limitation of functional communication training (FCT) is that after the functional communication response (FCR) is taught, the response may be emitted at high rates or inappropriate times. Thus, schedule thinning is often necessary. Previous research has demonstrated that multiple schedules can facilitate schedule thinning by establishing discriminative control of the communication response while maintaining low rates of problem behavior. To date, most applied research evaluating the clinical utility of multiple schedules has done so in the context of behavior maintained by positive reinforcement (e.g., attention or tangible items). This study examined the use of a multiple schedule with alternating Fixed Ratio (FR 1)/extinction (EXT) components for two individuals with developmental disabilities who emitted escape-maintained problem behavior. Although problem behavior remained low during all FCT and multiple schedule phases, the use of the multiple schedule alone did not result in discriminated manding.